2013
DOI: 10.1589/jpts.25.1223
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Clinically Important Difference for Comfortable Speed as a Measure of Gait Performance in Patients Undergoing Inpatient Rehabilitation after Stroke

Abstract: [Purpose] The purpose of this retrospective study was to determine the minimal clinically important difference for comfortable gait speed for patients with stroke. [Subjects] Data were analyzed from 35 patients undergoing inpatient rehabilitation. [Methods] Two characteristics of gait were measured, assistance required and comfortable gait speed. Patients were grouped as either experiencing or not experiencing a decrease of 2 or more levels of assistance required over the course of rehabilitation. Receiver ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 9 publications
0
40
0
3
Order By: Relevance
“…A second study has also indicated that an improvement in gait speed of 0.13 m/s or more, over the course of rehabilitation, is clinically important in people with stroke. 25 In addition, the improvement in walking speed was accompanied by an improvement in stride length, which suggests that the addition of cueing of cadence to walking training is not detrimental to the quality of movement. This is an important finding because clinicians have been cautious about increasing the tempo of beats during walking training in case any increases in cadence and speed occur at the expense of stride length, which would be undesirable.…”
Section: Discussionmentioning
confidence: 96%
“…A second study has also indicated that an improvement in gait speed of 0.13 m/s or more, over the course of rehabilitation, is clinically important in people with stroke. 25 In addition, the improvement in walking speed was accompanied by an improvement in stride length, which suggests that the addition of cueing of cadence to walking training is not detrimental to the quality of movement. This is an important finding because clinicians have been cautious about increasing the tempo of beats during walking training in case any increases in cadence and speed occur at the expense of stride length, which would be undesirable.…”
Section: Discussionmentioning
confidence: 96%
“…44,45 In this study, the mean change in walking speed created by the SMA was 9.51 cm/s (95% confidence interval, 5.66-13.35 cm/s); therefore, it was smaller than the generally regarded minimum clinically important difference of 13 cm/s for the comfortable walking speed of stroke patients. 21 It has been noted that the effectiveness of RAGT may increase with longer periods and higher movement intensities. The 10-day period of RAGT used in the present study was shorter than the frequently used period of 3-4 weeks 46 ; therefore, its movement intensity may have been insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…The minimum clinically important difference in walking speed of hospitalized rehabilitation stroke patients is considered 13 cm/s. 21 Using a pilot study, 22 we found a mean maximum walking speed of 68.5 cm/s (standard deviation [SD], §14.3 cm/s). We used OpenEpi 23 to calculate the sample size and assumed a minimum clinically important difference of 13 cm/s for speed between the control group and the SMA group.…”
Section: Sample Sizementioning
confidence: 99%
“…Figure 2 summarizes the yield of the search process. Of 62 articles identified as potentially relevant by the database and hand searches or recommendations by the expert, seven were ultimately included in our summary [21][22][23][24][25][26][27]. Table 2 summarizes the studies.…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%